2009
DOI: 10.1186/1758-2652-12-33
|View full text |Cite
|
Sign up to set email alerts
|

Variables that influence HIV‐1 cerebrospinal fluid viral load in cryptococcal meningitis: a linear regression analysis

Abstract: BackgroundThe central nervous system is considered a sanctuary site for HIV-1 replication. Variables associated with HIV cerebrospinal fluid (CSF) viral load in the context of opportunistic CNS infections are poorly understood. Our objective was to evaluate the relation between: (1) CSF HIV-1 viral load and CSF cytological and biochemical characteristics (leukocyte count, protein concentration, cryptococcal antigen titer); (2) CSF HIV-1 viral load and HIV-1 plasma viral load; and (3) CSF leukocyte count and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Opportunistic infections of the CNS such as tuberculosis meningitis (TBM) have been shown to play a critical role in HIV compartmentalization [6]; however, there is limited evidence on whether or not cryptococcal meningitis (CM) have similar effects. Previous studies have shown that inflammation of the meninges caused by CM may result in the disruption of the blood-brain barrier (BBB), thereby causing the HIV-infected cells to easily penetrate the barrier into the CNS [7,8]. Once in the CNS, the virus may be subjected to different immune and/or drug pressure; however, whether or not the CNS quasispecies is distinct from those from peripheral blood is still not confirmed.…”
Section: Introductionmentioning
confidence: 99%
“…Opportunistic infections of the CNS such as tuberculosis meningitis (TBM) have been shown to play a critical role in HIV compartmentalization [6]; however, there is limited evidence on whether or not cryptococcal meningitis (CM) have similar effects. Previous studies have shown that inflammation of the meninges caused by CM may result in the disruption of the blood-brain barrier (BBB), thereby causing the HIV-infected cells to easily penetrate the barrier into the CNS [7,8]. Once in the CNS, the virus may be subjected to different immune and/or drug pressure; however, whether or not the CNS quasispecies is distinct from those from peripheral blood is still not confirmed.…”
Section: Introductionmentioning
confidence: 99%
“…The CSF cytological and biochemical characteristics were as follows: leukocyte count, 10 cells/mm 3 (4–23); glucose, 39 mg/dL (32.7-50); protein concentration 0.75 g/L (0.48-1.06); and Cryptococcus neoformans capsular polysaccharide antigen titer, 1/100 dilutions (1/10-1/1000). 9 Eighty-five percent of patients had a positive CSF India ink examination. No difference was observed between survivors and non survivors in the CSF cellularity (P=0.31), protein concentration (P=0.81) and Cryptococcus neoformans capsular polysaccharide antigen titer (P=0.27).…”
Section: Brief Reportmentioning
confidence: 99%
“…We previously reported on factors that influence CSF HIV-1 concentrations in patients with meningitis by Cryptococcus neoformans . 9 The purpose of the present investigation was to study HIV-1 dynamics during the first 3 weeks of antifungal therapy and to compare concentrations of HIV-1 in the CSF and in the plasma of patients with cryptococcal meningitis. We conducted a longitudinal observational study at a single center.…”
Section: Brief Reportmentioning
confidence: 99%
“…A small study previously demonstrated that HIV-infected patients coinfected with CM have higher CSF viral loads compared with those monoinfected with HIV [ 8 ]. Another found no correlation between CSF cryptococcal antigen and CSF HIV viral load [ 9 ].…”
mentioning
confidence: 99%